2016
DOI: 10.12965/jer.1632692.346
|View full text |Cite
|
Sign up to set email alerts
|

Treadmill exercise ameliorates intracerebral hemorrhage-induced depression in rats

Abstract: Intracerebral hemorrhage (ICH) is a severe type of stroke causing neurological dysfunction with high mortality rate. Depression is one of the most common complications of ICH. In the present study, the effects of treadmill exercise on ICH-induced depressive symptoms in relation with apoptosis were investigated using rats. ICH rat model was induced by injection of collagenase into the hippocampus using stereotaxic instrument. Open field test for activity and forced swimming test for depressive symptoms were con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 35 publications
(54 reference statements)
1
25
0
Order By: Relevance
“…In the present study, mice submitted to exercise showed higher levels of serotonin turnover. This is in agreement with a previous report showing an improvement of depressive symptoms and high striatal serotonin turnover after aerobic exercise [17,46]. Clinical study shows that unmedicated patients with major depression show higher serotonin turnover levels [47].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, mice submitted to exercise showed higher levels of serotonin turnover. This is in agreement with a previous report showing an improvement of depressive symptoms and high striatal serotonin turnover after aerobic exercise [17,46]. Clinical study shows that unmedicated patients with major depression show higher serotonin turnover levels [47].…”
Section: Discussionsupporting
confidence: 93%
“…Physical exercise positively modifies mood symptoms and mobility [16,17]. Moreover, exercise improves sleep quality [18], memory [19] and influences anti-inflammatory activity [20].…”
Section: Introductionmentioning
confidence: 99%
“…Two molecules, known as Bax (pro-apoptotic molecule) and Bcl-2 (anti-apoptotic molecule), regulate the process of apoptotic cell death. During the apoptosis process, Bax is largely expressed and then promotes cell death, in contrast, Bcl-2 exerts a protective effect against cell death [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The forced swimming test was performed to evaluate the rats' depressive state, according to a previously described method (Sung et al 2010;Roh et al 2016). On the day after the sexual behavior test, the rats were exposed to a 6-minute test, in which they were placed individually in a vertical Plexiglas cylinder (height, 45 cm; diameter, 19 cm) filled to a height of 30 cm with water at 26°C ± 1°C.…”
Section: Forced Swimming Testmentioning
confidence: 99%
“…To detect 5-HT-positive and TPH-positive cells in the dorsal raphe, immunohistochemistry was performed, following a previously described method (Seo et al 2013;Roh et al 2016). On average, 6 sections were selected in each brain.…”
Section: Immunohistochemistry For 5-ht and Tphmentioning
confidence: 99%